2013
DOI: 10.3945/ajcn.113.061432
|View full text |Cite
|
Sign up to set email alerts
|

The association between MTHFR 677C>T genotype and folate status and genomic and gene-specific DNA methylation in the colon of individuals without colorectal neoplasia

Abstract: Background: Decreased genomic and increased gene-specific DNA methylation predispose to colorectal cancer. Dietary folate intake and the methylenetetrahydrofolate reductase polymorphism (MTHFR 677C>T) may influence risk by modifying DNA methylation.Objective: We investigated the associations between MTHFR 677C>T genotype, folate status, and DNA methylation in the colon.Design: We conducted a cross-sectional study of 336 men and women (age 19–92 y) in the United Kingdom without colorectal neoplasia. We obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 48 publications
1
11
0
1
Order By: Relevance
“…They observed no effect of folate status biomarkers on the CGI methylation of either gene but obtained some evidence of an inverse relationship between vitamin B12, which is also a factor in SAM metabolism, and methylation of ESR1. In a larger study of 336 men and women without colorectal neoplasia, Hanks et al found no effect of plasma folate, RBC folate or plasma homocysteine on global methylation, or on CGI methylation of ESR1, MYOD1, IGF2, N33, APC or MLH1, but they did observe a weak inverse relationship between serum folate and methylation of MGMT [58]. The possibility of a relationship between MTHFR 677C>T genotype and DNA methylation status was also examined in this study but no evidence of an effect was observed.…”
Section: Long-term Nutritional Status and Dna Methylation In The Human Gutmentioning
confidence: 94%
“…They observed no effect of folate status biomarkers on the CGI methylation of either gene but obtained some evidence of an inverse relationship between vitamin B12, which is also a factor in SAM metabolism, and methylation of ESR1. In a larger study of 336 men and women without colorectal neoplasia, Hanks et al found no effect of plasma folate, RBC folate or plasma homocysteine on global methylation, or on CGI methylation of ESR1, MYOD1, IGF2, N33, APC or MLH1, but they did observe a weak inverse relationship between serum folate and methylation of MGMT [58]. The possibility of a relationship between MTHFR 677C>T genotype and DNA methylation status was also examined in this study but no evidence of an effect was observed.…”
Section: Long-term Nutritional Status and Dna Methylation In The Human Gutmentioning
confidence: 94%
“…Folate metabolisms is involved in various intracellular processes such as DNA methylation, cell proliferation and synthesis of nucleic and amino acids [179]. Genetic alterations in these genes may disrupt folate metabolism function, inducing DNA hypomethylation and consequently activating proto-oncogenes [180][181][182][183][184]. Thus, polymorphisms in folate metabolism genes may promote tumor development and modify sensitivity of tumor cells to platinum compounds.…”
Section: Folate Metabolismmentioning
confidence: 99%
“…MTHFR is a crucial enzyme in the folate metabolism. Several polymorphisms in this gene lead to a production of an enzyme with decreased activity and their effects have been linked with DNA hypomethylation, therefore influencing platinum therapy outcomes [180][181][182][183][184].…”
Section: Mthfrmentioning
confidence: 99%
“…Polymorphisms of folate cycle enzymes are considered as a significant reason for thegenetic locationto the development of autistic disorders 6,7 . In addition, polymorphisms of genes involved in thefolic acid cycle are associated with hyperhomocysteinemia, cardiovascular catastrophes 8 and the later stage of dementia 9 , congenital anomalies, primarily the nervous system 5,10 , and pathology in pregnancy, including multiple spontaneous abortions 11 , a high risk of cancer developing, including colon and rectal 12 , due to a DNA methylation [13][14][15] . There are few reports of autism in adults and children suffered from Neuroinfectious diseases, mainly the opportunistic infections 10,16 .…”
Section: Introductionmentioning
confidence: 99%